만성편두통 및 만성긴장성두통 치료에 있어 성상신경절차단의 효과 비교 - 최원준; Won Joon Choi; 정준영; Jun Young Chung; 이두익; Doo Ik Lee; 신옥영; Ok Young Shin; 김동수; Dong Soo Kim (Korean journal of anesthesiology, 2006)
Background: The treatment for chronic headache is not simple because of the complexity of its cause and etiology. A stellate ganglion block (SGB) is normally used to treat chronic headache. This study compared the effectiveness of SGB in treating tension headache and migraine patients by evaluating its effect on pain alleviation and improving the quality of life after an 8 week treatment duration. Methods: Forty-six patients, who experienced headache for more than 4 hours a day and more than 15 days a month and were diagnosed with chronic headache, were enrolled in this study. The patients were classified into two groups, the migraine group (MG, n=26) and the tension headache group (TG, n=20). The patients were treated with SGB only and the degree of pain was evaluated after 4 and 8 weeks of treatment, and 4 weeks after the end of treatment. The treatment was applied twice a week during 8 weeks. The effects of these treatments in the two groups were analyzed using Visual Analogue Scale (VAS) pain scores and Brief Pain Inventory (BPI). Results: The VAS and BPI after 8 weeks of treatment showed significant differences compared with those of MG and TG before treatment, and there were no differences between the two groups. The VAS and BPI of the two groups, 4 weeks after the end of treatment, showed statistically significant improvement compared with those before treatment. Conclusions: The above results suggested that SGB might be an useful modality for the alleviating the pain and improving the quality of life in TG and MG patients. (Korean J Anesthesiol 2006; 51: 201~6)